Identification of a novel gene involved in stable maintenance of plasmid pGA1 from Corynebacterium glutamicum - Venkova, T; Pátek, M; Nesvera, J (Plasmid, 2001)
The cryptic plasmid pGA1 (4.8 kb) from Corynebacterium glutamicum, replicating in the rolling-circle mode, has been reported to contain four open reading frames longer than 200 bp (ORFA/per, ORFA2, ORFB, ORFC/rep). Here we present another pGA1 gene, ORFE (174 bp), located in the region downstream of the per-ORFA2 gene cluster. The ORFE is transcribed into two RNA species in a direction opposite to that of the per-ORFA2 RNA. Introduction of ORFE in trans into the cells harboring the pGA1 derivatives carrying the main stability determinant, the per gene coding for a product that positively influences the pGA1 copy number and maintenance, increased their segregational stability. Mutation of the putative translational start of the ORFE abolished this observed positive effect in trans. ORFE thus codes for a protein acting as an accessory element involved in stable maintenance of plasmid pGA1 and was hence designated the aes gene (accessory effector of stable maintenance).
Keywords: genetická transkripce; Open Reading Frames; exprese genu; DNA bakterií; sekvence nukleotidů; Corynebacterium; messenger RNA; Gene Expression; Genes, Bacterial; Molecular Sequence Data; Transcription, Genetic; molekulární sekvence - údaje; bakteriální RNA; plazmidy; bakteriální proteiny; Amino Acid Sequence; RNA, Messenger; DNA, Bacterial; Base Sequence; bakteriální geny; Bacterial Proteins; otevřené čtecí rámce; Plasmids; RNA, Bacterial; sekvence aminokyselin